THE INFLUENCE OF WORK ABILITY, WORK ETHOS AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT GARMENT INDUSTRIES IN JOMBANG INDONESIA - Novi Kurniawati; Siti Mujanah (Universitas Dinamika, 2021)
The purpose of this study was to determine the effect of work ability, work ethic and work environment on employee performance. This study usesquantitative methods. Total population and samples are 50 respondents from all employees Garment Industries. The data analysis technique used is Multiple Linear Regression Analysis. The t test results show that work ability, has a positive and significant effect on employee performance, work etnic has a positive and significant effect on employee performance, and work environment has a positive and significant effect on employee performance. And the results of the F show that the variables of Self Ability, work etnic and work environment simultaneously affect the Employee Performance OF Garmen Industries